2011
DOI: 10.1021/bi2014618
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the 2-Aminopurine-Cytosine Base Pair Formed in the Polymerase Active Site of the RB69 Y567A-DNA Polymerase

Abstract: The adenine base analog 2-aminopurine (2AP) is a potent base substitution mutagen in prokaryotes because of increased ability to form a mutagenic base pair with an incoming dCTP. Despite more than 50 years of research, the structure of the 2AP-C base pair remains unclear. We report the structure of the 2AP-dCTP base pair formed within the polymerase active site of the RB69 Y567A-DNA polymerase. A modified wobble 2AP-C base pair was detected with one H-bond between the N1 of 2AP and a proton from the C4 amino g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 59 publications
0
28
0
Order By: Relevance
“…The structure that we have reported for a dATP/dT-containing ternary complex of Y567A RB69pol shows that the minor groove HB network at the n-1 position of the template strand and the pol was disrupted by replacing Y567 with Ala. (37, 39) It is very likely that the Y567A RB69pol mutant was not able to sense the dA to 3DA substitution at this position. As predicted, the kinetic parameters for incorporation of dAMP opposite dT by the Y567A RB69pol mutant were almost identical for both control DNA and DNA with 3DA at the n-1 position of the template strand (Table 2).…”
Section: Results and Disscusionmentioning
confidence: 94%
See 1 more Smart Citation
“…The structure that we have reported for a dATP/dT-containing ternary complex of Y567A RB69pol shows that the minor groove HB network at the n-1 position of the template strand and the pol was disrupted by replacing Y567 with Ala. (37, 39) It is very likely that the Y567A RB69pol mutant was not able to sense the dA to 3DA substitution at this position. As predicted, the kinetic parameters for incorporation of dAMP opposite dT by the Y567A RB69pol mutant were almost identical for both control DNA and DNA with 3DA at the n-1 position of the template strand (Table 2).…”
Section: Results and Disscusionmentioning
confidence: 94%
“…(39) The excitation and emission wavelengths for tC o are 364 nm and 450 nm respectively. The final reaction mixtures consisted of 50 mM Tris (pH7.4), 10 mM MgSO 4 , 200 nM P/T and 4 µM RB69pol.…”
Section: Methodsmentioning
confidence: 99%
“…Human mitochondrial promoters present an extra challenge because the DNA region upstream of the transcription start-sites is GC rich, unlike the T7 and yeast mitochondrial promoters. Fortunately, the fluorescent base 2-AP pairs with both thymine and cytosine bases (Figure 4B ) ( 45 , 46 ) and hence can be used on human mitochondrial promoters. The desirable property of 2-AP is that its fluorescence is quenched in duplex DNA and enhanced when the 2-AP base pair is melted and unstacked.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous structural and kinetic studies with 2AP, a fluorescent adenine analog, have shown that 2AP fluorescence is quenched as dTTP binds to an RB69pol-P/T binary complex with 2AP as the templating base and a dideoxy-terminated ddC at the 3′-end of the primer (16,34). We have interpreted the fluorescence quenching by dTTP as a consequence of 2AP stacking with the penultimate base pair as the fingers domain closes.…”
Section: Resultsmentioning
confidence: 99%